2014
DOI: 10.1289/ehp.1307260
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Next Generation of Risk Science

Abstract: Objectives: In 2011, the U.S. Environmental Protection Agency initiated the NexGen project to develop a new paradigm for the next generation of risk science.Methods: The NexGen framework was built on three cornerstones: the availability of new data on toxicity pathways made possible by fundamental advances in basic biology and toxicological science, the incorporation of a population health perspective that recognizes that most adverse health outcomes involve multiple determinants, and a renewed focus on new ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 61 publications
(96 reference statements)
1
95
0
Order By: Relevance
“…"Next Generation Risk Science" research highlights the importance of assessing risks and challenging situations using innovative methodologies and addressing them using multiple interventions. 8 This population-level approach can be personalized into readiness and performance elements. As a starting point, several experienced global health researchers, before and during CCGH, provided input to build three case studies to present both at CCGH and at the SYP Summit.…”
Section: Global Health Researchers' Operational Readiness Profile Chamentioning
confidence: 99%
“…"Next Generation Risk Science" research highlights the importance of assessing risks and challenging situations using innovative methodologies and addressing them using multiple interventions. 8 This population-level approach can be personalized into readiness and performance elements. As a starting point, several experienced global health researchers, before and during CCGH, provided input to build three case studies to present both at CCGH and at the SYP Summit.…”
Section: Global Health Researchers' Operational Readiness Profile Chamentioning
confidence: 99%
“…The NexGen framework for risk-based decision-making aims to transform the human health risk assessment process to one that focuses on characterising risk of critical toxicity pathway perturbations. Based on the illustrative examples, there is already a transition in the technologies that are being incorporated into toxicity testing and risk assessment paradigms (Krewski et al, 2014).…”
Section: Challenge 2: Can Toxicity Pathways Predict Adverse Outcomesmentioning
confidence: 99%
“…It was hypothesised that the evolution in toxicity testing would provide new methodologies to support broad characterisation of chemicals, including toxicity end points or outcomes, life stage analysis, and analysis of chemical mixtures. A robust scientific basis for environmental health risk assessments would be developed by amalgamating data on mode of action, dose-response, and human exposure-based primarily on in vitro testing, computational systems biology pathway models and expanded use of high-throughput (HT) biomonitoring data, respectively (Krewski et al, 2014). New scientific approaches were also acknowledged in the lectures by Hartung and Meunier, including the added benefit of reducing the use of animal models for testing (Schoeters, 2010;Hartung and McBride, 2011;Bouhifd et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(US EPA, 2012). Krewski et al (2011) have shown that these new tools and technologies are compatible with the well-established risk assessment paradigm laid out in the 1983 Red Book and case studies have demonstrated the feasibility of using these new methods for risk assessment (Krewski et al, 2014). Although these in vitro methods are not yet able to identify hazardous chemicals directly, this remains a possibility in the future.…”
Section: Introductionmentioning
confidence: 97%
“…Building on the context provided by the preceding historical perspective, the objective of this paper is to describe the development of the NexGen framework recently published in detail (Krewski et al, 2014), which merges key contributions of three previously published frameworks. These frameworks are: 1 the NRC vision framework for toxicity testing (TT21C) (National Research Council, 2007), which promotes an evidence-based approach to risk assessment based on high throughput in vitro methods combined with in silico computation 2 the framework for population health risk assessment (Krewski et al, 2007;Chiu et al, 2013), which represents a first attempt to integrate the fields of risk science and population health 3 the Science and Decisions framework for the advancement of risk assessment (National Research Council, 2009), which outlines new directions in the design and conduct of risk assessment of environmental agents.…”
Section: Introductionmentioning
confidence: 99%